2015
DOI: 10.1002/wcm.2635
|View full text |Cite
|
Sign up to set email alerts
|

Energy Efficiency Architecture Design for Heterogeneous Cellular Networks

Abstract: Heterogeneous cellular networks (HetNets) have emerged as a new promising paradigm to further enhance capacity, where multiple types of low power smallcells are overlaid in a high power macrocell. They provide more opportunities to explore the potential cognition and cooperation diversities to improve the spectral efficiency. On the other hand, energy efficiency is a critical performance metric, which deserves more attention from academia, industry, and standardization, in particular, in scenarios where smallc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…To meet the higher data rate and reliable connectivity, service providers are increasingly using macro-cells, pico-cells, femto-cells, and micro-cells in ultra dense small cell networks (UDSCNs). 17 In a recent survey, [18][19][20] it is found that more than 50% of the energy is consumed at the base station for wireless communication. Hence, the s-BS sleep strategy is used to minimize power consumption, and reduction in the deployment of s-BSs.…”
Section: Related Workmentioning
confidence: 99%
“…To meet the higher data rate and reliable connectivity, service providers are increasingly using macro-cells, pico-cells, femto-cells, and micro-cells in ultra dense small cell networks (UDSCNs). 17 In a recent survey, [18][19][20] it is found that more than 50% of the energy is consumed at the base station for wireless communication. Hence, the s-BS sleep strategy is used to minimize power consumption, and reduction in the deployment of s-BSs.…”
Section: Related Workmentioning
confidence: 99%
“…In this example, we will study the effect of the number of available relays on the analyses of the outage probability and probability of spoofing detection. To achieve this, we consider six available relay nodes in our scenario which are placed in order at (5, 0), (5, 1), (5,2), (5,3), (5,4), and (5, 5), respectively. Moreover, the position of Eve is fixed at (−5, 0).…”
Section: Example 2: Effect Of the Number Of Available Relaysmentioning
confidence: 99%
“…During the recent past, wireless networks have experienced a rapid growth in data traffic which is spurred by an explosive increase in the number of diverse devices. To accommodate such increases in devices in future fifth generation (5G) wireless communications, heterogeneity is expected as an important feature that characterizes the future 5G networks by deploying dense small cells underlaid in macrocell cellular networks with coexistence of device-todevice (D2D) communications [1][2][3][4]. This enables enhanced radio coverage and different levels of coordination between different types of devices.…”
Section: Introductionmentioning
confidence: 99%
“…This metric contains a careful treatment of the capital expenditure (CapEx) and operational expenditure (OpEx) of the wireless network. For a core network, which cares more about the capacity, the SE is more suitable for explaining the relationship between the capacity and the energy consumption [ 16 ].…”
Section: Introductionmentioning
confidence: 99%